The role of teachers in enhancing the extrinsic motivation of grade X students at SMK Negeri 3 Rantau Utara - Uswatun Hasanah Rambe; Siti Zahara Saragih (Privietlab, 2023)
This research, conducted at SMK Negeri 3 Rantau Utara, illuminates the crucial role teachers play in elevating educational quality, specifically focusing on extrinsic learning motivation for Grade X students. Using a purposive sampling approach, the study engaged 1 teacher and 20 students to discern the broader implications of a teacher's role beyond traditional instruction. Findings highlighted teachers' dual capacities as